Healing pattern of intentional pterygoid plate fracture after posterior movement of maxilla through Le Fort I osteotomy. Issue 10 (October 2018) - Choi, Na-Rae; Shin, Sang-Hun; Kim, Seong-Sik; Sandor, George; Kim, Yong-Deok
Abstract: Background: To evaluate maxillary stability following Le Fort I osteotomy using postero-superior movement after pterygoid plate fracture. Additionally the authors sought to analyze the postoperative changes at the intentional pterygoid plate fracture site. Materials and methods: Thirty-six patients with class III deformities treated with total maxillary setback at the Lefort I level were enrolled in a retrospective cohort study. Relative changes in measurement points were identified on cone-beam computed tomographic scans (CBCT) as well as lateral cephalograms. The outcome variables were determined as changes at measurement points obtained preoperatively, immediately postoperatively, and 6 months after surgery. Results: The average posterior repositioning of ANS in the 36 patients was 1.78 mm and the mean superior repositioning at PNS was 2.78 mm. The maximal recurrence rate was less than 10% at the 6 months postoperative time point. The intentional fracture site of the pterygoid plates healed with a linear pattern. There were no major complications such as airway edema, hemorrhage and nerve damage reported over the 6-month follow-up period. Conclusions: Intentional fracture of the pterygoid plates has a role in the retropositioning of the maxilla with good healing at the fracture site, little relapse and satisfactory postoperative stability.